Comparison of Canine and Feline Meningiomas Using the Apparent Diffusion Coefficient and Fractional Anisotropy - Wada, Masae; Hasegawa, Daisuke; Hamamoto, Yuji; Yu, Yoshihiko; Asada, Rikako; Fujiwara-Igarashi, Aki; Fujita, Michio (Frontiers in Veterinary Science, 2021)
Meningiomas are the most common intracranial tumor in dogs and cats, and their surgical resection is often performed because they are present on the brain surface. Typical meningiomas show comparatively characteristic magnetic resonance imaging findings that lead to clinical diagnosis; however, it is necessary to capture not only macroscopic changes but also microstructural changes to devise a strategy for surgical resection and/or quality of removal. To visualize such microstructural changes, diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) have been used in human medicine. The aim of this retrospective study was to investigate the different characteristics of the apparent diffusion coefficient (ADC) from DWI and fractional anisotropy (FA) from DTI of meningioma between dogs and cats. Statistical analyses were performed to compare ADC and FA values between the intratumoral or peritumoral regions and normal-appearing white matter (NAWM) among 13 dogs (12 lesions) and 6 cats (7 lesions). The NAWM of cats had a significantly lower ADC and higher FA compared to dogs. Therefore, for a comparison between dogs and cats, we used ADC and FA ratios that were calculated by dividing the subject (intra- or peritumoral) ADC and FA values by those of NAWM on the contralateral side. Regarding the intratumoral region, feline meningiomas showed a significantly lower ADC ratio and higher FA ratio than canine meningiomas. This study suggested that ADC and FA may be able to distinguish a meningioma that is solid and easy to detach, like as typical feline meningiomas.